Mikrofinanzierungen: Chancen für die Entwicklungspolitik und Rahmenbedingungen für einen effizienten Einsatz - Paul P. Maeser (Fachhochschule für Wirtschaft Berlin, IMB Institute of Management Berlin, 2008)
This paper deals with the opportunities of microfinance for developing countries and examines the necessary framework for a successful implementation of a microcredit program. The study asks what must be fulfilled in advance in order to make microfinance a valuable support for developing politics. In addition, the survey compares microfinance to other, more traditional instruments of economic cooperation and demonstrates why a combination of them can be both useful and destructive. With regard to these findings, two case studies present practical experience with microfinance institutes and analyze the projects on their effectiveness. The research paper infers that microfinance is a useful tool to fight poverty but its possible effects are mostly limited on income enhancement and stabilization only, whereas it cannot be expected that a microfinance strategy alone will lead to, e.g. a women's empowerment or better educational opportunities. Additionally, the survey comes to the conclusion that the success of a microfinance program is mostly dependent on stable prices, the embedment into a coordinated development strategy and sound legal conditions, such as the existence of property rights.
Keywords: 330